Atom probe tomography of metallic nanostructures. (January 2016) - Hono, Kazuhiro; Raabe, Dierk; Ringer, Simon P.; Seidman, David N.
Abstract: Abstract : This article focuses on four topics that demonstrate the importance of atom probe tomography for obtaining nanostructural information that provides deep insights into the structures of metallic alloys, leading to a better understanding of their properties. First, we discuss the microstructure–coercivity relationship of Nd-Fe-B permanent magnets, essential for developing a higher coercivity magnet. Second, we address equilibrium segregation at grain boundaries with the aim of manipulating their interfacial structure, energies, compositions, and properties, thereby enabling beneficial material behavior. Third, recent progress in the search to extend the performance and practicality of the next generation of advanced high-strength steels is discussed. Finally, a study of the temporal evolution of a Ni-Al-Cr alloy through the stages of nucleation, growth, and coarsening (Ostwald ripening) and its relationship with the predictions of a model for quasi-stationary coarsening is described. This information is critical for understanding high-temperature mechanical properties of the material.